Management and Utilisation of Land Resources to Attain Economic Sustainability among Christians in West Ankole Diocese, Uganda. - Ahereza, Madelean; Ocan, Johnson; Adyanga, Francis Akena (Kabale University, 2024)
The study set out to investigate the land resources that are accessible in the West Ankole Diocese, their management and use, and the obstacles that stand in the way of the diocese achieving the targeted level of economic sustainability. Districts of Bushenyi, Sheema, Mitooma, Rubirizi, and Buhweju, form the Greater Bushenyi area which is all included in the West Ankole diocese. The study incorporated qualitative as well as quantitative techniques, such as the observation method, focus groups, and one-on-one interviews. Using these methods, researchers observed the behavior of study participants and made inferences about their responses and operations. It was anticipated that the primary conclusions of the results would clarify some shortcomings, highlighting gaps in the methods used for the utilization of terrestrial resources, which resulted in development imbalances, high rates of malnutrition, and food shortages while other resources remained idle. The reasons for this were further explored, and potential mitigation strategies were put forth. In terms of contribution, this study suggested regulated population expansion, informed instruction in contemporary land use, and a shift in land ownership. The limitations of the study concluded that the problems addressed in this research and the suggestions presented provide the basis for improving the land use practices being conducted. The study looked for novel strategies that, if adopted, would enhance the economic livelihoods in West Ankole Diocese and raise living standards and sustainably generate income. It also identified land resource practices that have contributed to underdevelopment. According to the study, in order to achieve sustainable growth through the use of land resources, the diocese would eventually generate higher economic gains from the resources if the relevant authorities were empowered. The research has been carried out in Uganda for the first time, despite being founded on a review of pertinent papers.